CHINA IN CENTRAL ASIA: FROM TRADE TO STRATEGIC PARTNERSHIP - SYROEZHKIN, Konstantin (CENTRAL ASIA AND THE CAUCASUS, 2007)
Today China leaves no one indifferent: some experts are overenthusiastic about its socioeconomic reforms, while others fear the threats stemming from the country’s new role in the world. Both groups have a right to their opinion, but in real life nothing is ever quite so black and white.China is a dynamically developing country, but its “growing might” should not be overestimated: it is accompanied by growing problems. I am convinced, first, that in the context of world and regional security, these problems taken together are much more ponderous than “China’s might.”1Second, all those who tend to overestimate “China’s might” are breeding irrational fears and all sorts of phobias, are not allowing the world to adequately assess the country’s foreign policy, and are reviving fears of “China’s demographic and economic threat to the countries it borders on.” This is obviously an overstatement. China’sstronger economic position in Central Asia as a whole and in Kazakhstan in particular has become obvious, but not dramatic. Its share of foreign direct investments and foreign trade volume in Kazakhstan do not exceed 10 percent.2 China’s share in the other Central Asian countries is even smaller. Today, China badly needs new sources of raw materials (energy resources in particular) and markets for its products. Central Asia (especially Kazakhstan) is highly attractive in both respects. The trade and economic relations between China and Central Asia are developing entirely within the worldwide economic globalization trends.It should be said in all justice that due to its specifics and the nature of the relations among the actors involved in the region, this process is potentially dangerous to national security. This is the background against which China’s presence in Central Asia is assessed.